Partial Neutralization of a Lupus Anticoagulant by Human Immunoglobulin - Carreras, L O; Pérez, G N; Martinuzzo, M E; Malan-Borel, I; Malbrän, A; Said, P B (Thrombosis and Haemostasis, 1990)
In a patient with a Lupus Anticoagulant (LA) and recurrent fetal loss, we observed a significant shortening of the APTT after high-dose intravenous immunoglobulin infusion (IVIg).The LA activity present in patient’s serum and purified IgG was partially neutralized by IVIg in a dose-dependent way. In addition, IgG purified from IVIg and its F(ab′)2 fragment neutralized LA activity of the patient’s IgG. In both cases, the neutralization was dose-dependent and it was obtained with similar molar ratiosThe “in vitro” neutralization of LA activity and the immediate shortening of the APTT after IVIg infusion, might be mediated through idiotypel antiidiotype interactions.On the other hand, the long-lasting effect of IVIg in this patient indicates that it may induce specific inhibition of autoantibody synthesis.We believe that IVIg should be considered as a therapeutic alternative for LA-related clinical disorders.